Mathematical Logic Integration Scheme in Ushul Fiqh - Faani, Arini Mayan; Mukmin, Muhammad Islahul; Masamah, Ulfa; Rohmanan, Muhammad (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This research is aimed to arrange an integration scheme between mathematical logic and ushul fiqh which focuses on the discussion of mafhum mukholafah. This study is designed by using a qualitative design, which conducted by using library research/literature study. It was carried out by collecting materials related to research from books, scientific journals, literature and other publications that were worthy of being used as sources for research studies by describing the data through several expert opinions. The results of this study indicate that there is an integration between mathematical logic and the science of mantiq, especially in the discussion of the inverse of a statement with mafhum mukholafah. However, there is also a gap between them, there are still objects of study in ushul fiqh that cannot be accommodated in mathematical logic.